Experimental evaluation of the effect of spatial position on the power of a 5W LED - Gutiérrez Domínguez, María Paula (2020)
This experiment evaluates the effect of the spatial position on the power of a 5W LED which was obtained using a radiometer. For this purpose, the radiant flow emitted by the LED was arranged, taken at different positioning angles and the distance from it from the sensing equipment. Statistical analysis for the validation of the obtained data was checked against the values provided by the manufacturer according to the specification sheet. Finally, the increase in tilt angle and distance resulted in a loss of radiant flow emitted by the LED by 99%.